2013
DOI: 10.3945/ajcn.113.060590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea buckthorn and bilberry on serum metabolites differ according to baseline metabolic profiles in overweight women: a randomized crossover trial

Abstract: Background: Berries are associated with health benefits. Little is known about the effect of baseline metabolome on the overall metabolic responses to berry intake.Objective: We studied the effects of berries on serum metabolome.Design: Eighty overweight women completed this randomized crossover study. During the interventions of 30 d, subjects consumed dried sea buckthorn berries (SBs), sea buckthorn oil (SBo), sea buckthorn phenolics ethanol extract mixed with maltodextrin (SBe+MD) (1:1), or frozen bilberrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 49 publications
0
33
0
1
Order By: Relevance
“…SB oil did not affect the circulating triacylglycerols or cholesterol. In our earlier study, SB oil lowered serum total, IDL, and LDL cholesterol and subfractions of IDL and LDL among women with a metabolic profile with a higher cardio-metabolic risk, whereas the effects among women with a lower risk profile at baseline were modest [7]. This study has limitations.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…SB oil did not affect the circulating triacylglycerols or cholesterol. In our earlier study, SB oil lowered serum total, IDL, and LDL cholesterol and subfractions of IDL and LDL among women with a metabolic profile with a higher cardio-metabolic risk, whereas the effects among women with a lower risk profile at baseline were modest [7]. This study has limitations.…”
Section: Discussionmentioning
confidence: 50%
“…Sea buckthorn (Hippophaë rhamnoides) oil has in the Central Asia traditionally been used for the treatment of inflammations in the genital organs and uterus [6]. Intake of sea buckthorn (SB) oil produced with a supercritical carbon dioxide extraction process has in clinical studies shown beneficial effects on serum lipids and lipoproteins [7], dry eye [8], markers of endothelial inflammation [9], and platelet aggregation [10]. In a double-blind, randomized, cross-over study in women suffering from Sjögren's syndrome, SB oil relieved the dryness-associated symptoms of genital mucous membranes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Different forms of SBs can contain different amount of vitamins, minerals as well as steroids, terpenoids, phenolics, fatty acids and other compounds making the comparison between these studies more difficult. Similarly, the exposure time varied from 30 days (Larmo et al, 2013) to 90 days (Larmo et al, 2009), which was the longest studied period. The control products used were also different in each of these studies.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…The participants of these studies were all healthy, normolipidemic men and/or women. In two studies, subjects were overweight or obese (Larmo et al, 2013;Lehtonen et al, 2011) and in only one study (Larmo et al, 2013), the subjects were separated into two groups based on their high or low risk for CVD.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Sea buckthorn oil induced a decreasing trend in the serum total cholesterol, intermediate-density lipoprotein (IDL), low-density lipoprotein (LDL) [46].…”
Section: Clinical Evidencesmentioning
confidence: 99%